Feasibility study of using a portable, high repetition rate fiber laser for laser-induced breakdown spectroscopy - Palásti Dávid Jenő (Proceedings of the International Symposium on Analytical and Environmental Problems, 2022)
Laser-induced breakdown spectroscopy (LIBS) is a dynamically evolving elemental analytical method, which has a great array of unique and advantageous features such as quickness, multi elemental detection, virtually none destructiveness and requires little to no sample preparation. The quick advancement of LIBS is partly due to the ever improving properties of pulsed laser sources. One laser type which went through a significant improvement in recent years are the fiber lasers. In this current study we investigate the performance characteristics and feasibility of using a fiber laser for the ignition of microplasmas.